Implementation of Child Protection Law in Elementary Madrasahs: A Qualitative Study of Readiness and Achievements - Hendar Hendar (Journal of General Education and Humanities, 2026)
The implementation of child protection in educational institutions is mandated by Undang-Undang Nomor 35 Tahun 2014, which requires all educational institutions, including madrasahs, to ensure the fulfillment of children's rights and protection. However, in practice, the implementation of this regulation continues to face various challenges, including at Madrasah Negeri 2 Karawang. This study aims to describe the level of institutional readiness in implementing child protection law and to identify the achievements and obstacles encountered in protecting students from various forms of violence and rights violations. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews with the head of the madrasah, teachers, and administrative staff, as well as observations of school activities and policies. The data were analyzed using thematic analysis to identify patterns and key findings related to the implementation of child protection policies. The results indicate that the madrasah has taken strategic steps to enhance its readiness, including the formulation of internal policies, the dissemination of child protection values, and the strengthening of supervision mechanisms. Nevertheless, several challenges remain, particularly in preventing and addressing physical and psychological violence. The level of child protection achievement is considered not yet optimal due to limited resources, insufficient training, and the absence of a comprehensive reporting system. Therefore, capacity building for teachers and educational staff, along with continuous policy support and supervision from the government, is necessary to strengthen the implementation of the child protection law in madrasahs.